Effects of Dietary Patterns, Weight Loss Diets, and Dietary Components on Serum Adiponectin Levels - Vajihe Izadi; Leila Azadbakht (مجله دانشکده پزشکی اصفهان, 2012)
Background: Adiponectin, an adipocytokine secreted by adipose tissue, is negatively related with body fat mass. It plays an important role in insulin sensitivity and improvement of lipid profile, cardiovascular diseases, and inflammation. We aimed to review the evidence of the correlation between dietary patterns, low-calorie diets, and dietary components on adiponectin levels. Methods: We used PubMed search engine to articles which were published during 2002-12 and contained the following keywords: dietary patterns, low calorie diets, omega-3 polyunsaturated fatty acids, dietary protein, dietary fat, and adiponectin. After search, 45 articles with cross-sectional, clinical trial, prospective, and experimental designs were recruited and reviewed. Findings: Adherence to healthy dietary patterns, such as Mediterranean dietary pattern, showed a positive relation with adiponectin level. Long-term low-calorie diet with at least 10% weight loss can improve the level of hormone. Likewise, consumption of omega-3 fatty acids had a significantly positively associated with adiponectin concentration. On the other hand, high-fat diets were potentially negatively correlated with the level of hormone. Although few investigations about dietary proteins and adiponectin were available, intake of millet, egg, and soy proteins were found to enhance the level of this hormone. Conclusion: Serum adiponectin level is positively related with several components of healthy dietary pattern, weight loss diet, and intake of omega-3 sources and dietary proteins such as egg, millet, and soy. It is negatively correlated with high fat diets. Keywords: Dietary pattern, Weight loss, Dietary components, Dietary carbohydrate, Serum adiponectin level